1998
DOI: 10.1044/0161-1461.2902.76
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Synthesis of the "Late Talker" Literature

Abstract: "Late talkers" are most often differentiated from their normally developing peers by their limited expressive lexicons. In the majority of the studies conducted on late talkers, these children are described as producing fewer than 50 words and/or producing limited word combinations by 24 months of age. The expressive language of some of the late talkers will eventually resemble their same-age peers; however, a substantial number of these children will continue to evidence difficulties with their expressive lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Previous meta‐analyses have examined the efficacy of treatment for school‐age children with language disorders (Cirrin and Gillam 2008), and for children with developmental speech and language delays/disorders (Law et al 2004) and two reviews have explored the characteristics of children with LLE (Desmarais et al 2008, Kelly 1998); however, no systematic reviews have examined the effects of language treatment specifically for children with LLE with an emphasis on techniques and outcomes that hold clinical significance for this group. The research questions are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta‐analyses have examined the efficacy of treatment for school‐age children with language disorders (Cirrin and Gillam 2008), and for children with developmental speech and language delays/disorders (Law et al 2004) and two reviews have explored the characteristics of children with LLE (Desmarais et al 2008, Kelly 1998); however, no systematic reviews have examined the effects of language treatment specifically for children with LLE with an emphasis on techniques and outcomes that hold clinical significance for this group. The research questions are as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Studies of gesture in Spanishspeaking toddlers have found that children with or at risk for DLDs demonstrate significantly less conventional (culture specific) and iconic (object depicting) gesture usage, in addition to fewer gesture and word combinations. [13][14][15][16][17] Research has also shown that children with DLDs have delayed play skills including diminished symbolic play and lower levels of complexity of play than typical same-aged peers. [18][19][20] A recent study of typical and DLD Spanish-speaking children revealed complexity of play skills was significantly associated with language scores.…”
Section: Toddler Language Screening Measuresmentioning
confidence: 99%
“…14 Language sample measures including mean length of utterance in words (MLU-W) and number of different words (NDW) produced seem to capture early linguistic development and risk of DLDs in Spanish-speaking children, and can typically be observed from naturalistic or structured parent-child interactions. [14][15][16][17][18][19][20][21][22][23][24][25] There is evidence that Spanish-speaking parents in the United States are also accurate at identifying language learning difficulties in toddler and preschool-age children. 23,[26][27][28][29][30] A recent study reported classification accuracy values of 87% sensitivity and 86% specificity for a 100-item Spanish vocabulary parent checklist, the Inventarios del Desarrollo de Habilidades Comunicativas palabras y Enunciados (INV-II), as well as 91% sensitivity and 86% specificity for parent report of mean length of child's three longest utterances (RM3L).…”
Section: Toddler Language Screening Measuresmentioning
confidence: 99%
“…In contrast, it is also evident that, particularly for those with expressive delays, a proportion of children have a good chance of spontaneous resolution of their early oracy difficulties (Paul 1996). So although the body of knowledge which informs our understanding of which children are at risk is growing (see Kelly 1998, Olswang et al 1998, for recent summaries), evidence as to specifically which children it is necessary to target for intervention is still weak.…”
Section: Targeting Interventionmentioning
confidence: 99%